Economic feasibility of biochar for carbon stock enhancement in Finnish agricultural soils - Jokubė, Medilė; Hyyrynen, Matti; Pihlainen, Sampo; Hyytiäinen, Kari (Taylor & Francis, 2025)
Biochar is a promising climate mitigation measure that can safely capture and store atmospheric carbon dioxide in soil for many years. We conduct an economic analysis to assess the economic feasibility of increasing Finnish mineral agricultural soil carbon stock with biochar in an increasingly dry and warm climate scenario. The Monte Carlo simulations showed that it is challenging to achieve economic feasibility with current carbon prices and biochar costs. To make biochar application economically feasible with a carbon subsidy at the level of the European Union Emissions Trading System (EU ETS) carbon price of 88 EUR/t CO2eq, the cost of biochar material would need to be reduced to less than one-third of its current average price. Alternatively, economic viability could be achieved if the subsidy paid to the farmers was between two to nine times larger than the EU ETS carbon price for the current range of biochar market prices. Lastly, the feasibility can be achieved by simultaneous doubling of the carbon price and halving average biochar cost. Currently, the biochar market is thin and a decrease in biochar cost level is needed to make biochar competitive with other climate change mitigation measures.
Keywords: biochar; carbon dioxide removal; boreal; agricultural soil; carbon sinks